PENGARUH PENGELOLAAN KEARSIPAN TERHADAP EFISIENSI KERJA DI KANTOR PERPUSTAKAAN DESA WANASARI KECAMATAN MUARA WAHAU - Irnawati Irnawati (ADMINISTRASI PUBLIK, 2018)
Administrative activities in an office basically also have a result like other units. Results or products from an office are letters, forms, and reports. The management of the letters, forms, and reports produced and received by an office will ultimately relate to archives. So, the administrative activity is basically produce, receive, process, and store various letters, forms, reports and so forth. Wanasari Village Library Office Muara Wahau District is one of the government offices that serve the public interest that will not be separated from archival activities. Office that daily takes care of making library member cards, storing documents or other letters, making the office has a variety of archives. Success in archival management is determined by many things. Filing factors such as storage systems, archiving employees, archival equipment, and of course with the work environment. The management of archives conducted in the Wanasari Village Library Office of Muara Wahau Subdistrict is very influential to the success or failure of the rediscovery of archives.